POLA OKUPASI GUA KIDANG, JELAJAH RUANG DAN WAKTU: SUATU HIPOTESIS - Nurani, Indah Asikin; Hascaryo, Agus Tri Hascaryo (BRIN, 2012)
Kidang cave in the karst region Todanan, Blora, Central Java is a cave complex which consists of two caves. Archaeological findings show intensively inhabited this cave for a long time. Evidence of activity traces left behind in the form of artifacts, ekofak, features, skeleton (grave), and a fireplace. Pulling from landuse caves man and cave dwellers Kidang roaming in search of food sources and raw materials for tools, encouraging the cultural continuity with Pleistocene sites. Geological and archaeological data shed some light on the Kidang cave man roaming in the span of space and time with Pleistocene sites. A hypothesis of continuity between Pleistocene sites with Kidang cave will be formulated based on geo archaeological study.